The early life of borrowed path verbs in English - Huber, Judith (Motion and Space across Languages. Theory and applications, 2017)
In the Middle English period, a number of pure path verbs (e.g. enter, issue, descend, ascend) were borrowed from French and Latin into English. An analysis of the Old and Middle English motion verb inventory reveals that before this, pure path verbs hardly existed; an analysis of c. 1,000 Old and Middle English motion descriptions shows that path information is typically expressed outside the verb. The borrowed path verbs are therefore a new pattern in the Middle English system of talking about motion. By comparing their use in autonomous Middle English texts and in texts translated from French or Latin, I show that in autonomous texts, they are more restricted to non-literal motion (such as ‘descend from one’s ancestors’) and to specific types of literal motion, while in the translations, they are more freely used for general literal motio
Keywords: borrowing; Middle English; Old English; translation